DIY furniture : a step-by-step guide - Stuart, Christopher (Laurence King Publishing, 2011)
Featuring 30 designs by leading designer-makers from around the world DIY Furniture shows you how to use simple techniques to make stunning designer furniture from scratch. All the projects can be easily assembled using the step-by-step guides from common materials which can be found at the local hardware store